Gender and organizational culture in the European Union: situation and prospects - Nuria Alonso Gallo; Nuria Alonso Gallo; Irene Gutiérrez López (Frontiers in Psychology, 2023)
In recent decades, there has been a massive incorporation of women into the labor market. However, the belief that certain jobs or business functions can be performed better by people of one gender than the other has not allowed for widespread changes in the business culture to achieve effective equality between women and men in companies. Examples of this are unequal access to employment, vertical and horizontal segregation in occupations, wage discrimination, problems in reconciling personal and professional life, or difficulties in accessing management positions in companies (glass ceiling). Other determinants of gender inequalities have been long working hours, as well as the presence of employees, characteristic of European business culture. The progress achieved to date began with the incorporation of women into the labor market under unequal conditions that soon called for the need to establish a regulatory framework to try to eradicate them. The legal status of women in Europe has undoubtedly improved as a result of the development of European regulations, which have been binding in the development of business policies in the Member States and have succeeded in modifying the organizational climate through proposals such as the development of Equality Plans or salary audits. Examples of the most recent legislative initiatives of the European Union on equality that affect business practices are Directive 2022/2041/EC on adequate minimum wages in the European Union or Directive 2022/2381/EC on a better gender balance among directors of listed companies. This study attempts to systematize the changes in the legislation on effective equality between men and women in business and to analyze its effect on organizational culture through the information available in the statistics on gender equality—mainly from the European Union—which gather quantitative and qualitative information on the adaptation of business culture to the new legal framework and the overcoming of gender stereotypes that have been guiding business management in the last decade.